Governance of Formal Zakat institution in Saudi Arabia - Abdulsalam Ahmed Sawmar; Mustafa Omar Mohammad (International Journal of Zakat, 2019)
This study investigates the issues pertaining to governance practices of the formal zakat institution in Saudi Arabia, GAZT. It also attempts to develop a framework which explains how to improve zakat compliance through good governance. In order to achieve its objectives, the study employs a content analysis of relevant literature and qualitative interviews. Specifically, a total of 21 interviews were conducted with zakat experts in Saudi Arabia who represent diverse backgrounds to explore the issues and factors related to zakat governance-compliance relationship. The findings of the interviews’ analysis suggested several issues that likely affect zakat payers’ compliance in the Saudi context. These issues included the lack of control mechanisms that guarantee zakat payers’ compliance, the perceived image of the GAZT role in relation to zakat, the lack of trust, and issues affecting the perceived procedural fairness. In addition, the analysis of the qualitative interviews was used to develop a framework that explains how to improve zakat compliance through good governance. This study contributes to the literature by investigating governance issues and challenges to improving zakat payers’ compliance. Also, it provides practical implications for zakat administrators, especially in Saudi Arabia, to address these issues and improve the effectiveness of the zakat authority.